Inhibition of morphine-induced cAMP overshoot: a cell-based assay model in a high-throughput format - Xia, Menghang (2011)
Opiates are potent analgesics but also drugs of abuse mainly because they produce euphoria. Chronic use of opiates results in the development of tolerance and dependence. Dr Marshall Nirenberg’s group at the National Institutes of Health (NIH) was the first to use a cellular model system of Neuroblastoma×Glioma hybrid cells (NG108-15) to study morphine addiction. They showed that opiates affect adenylyl cyclase (AC) by two opposing mechanisms mediated by the opiate receptor. Although the cellular mechanisms that cause addiction are not yet completely understood, the most observed correlative biochemical adaptation is the upregulation of adenylyl cyclase. This model also provides the opportunity to look for compounds which could dissociate the acute effect of opiates from the delayed response, upregulation of AC, and thus lead to the discovery of non-addictive drugs. To identify small molecule compounds that can inhibit morphine-induced cAMP overshoot, we have validated and optimized a cell-based assay in a high throughput format that measures cellular cAMP production after morphine withdrawal. The assay performed well in the 1536-well plate format. The LOPAC library of 1280 compounds was screened in this assay on a quantitative high throughput screening (qHTS) platform. A group of compounds that can inhibit morphine induced cAMP overshoot were identified. The most potent compounds are eight naloxone related compounds, including levallorphan tartrate, naloxonazine dihydrochloride, naloxone hydrochloride, naltrexone hydrochloride, and naltriben methanesulfonate. The qHTS approach we used in this study will be useful in identifying novel inhibitors of morphine induced addiction from a larger scale screening.